How Tool-Use Shapes Body Metric Representation: Evidence From Motor Training With and Without Robotic Assistance - Bruno, Valentina; Carpinella, Ilaria; Rabuffetti, Marco; De Giuli, Lorenzo; Sinigaglia, Corrado; Garbarini, Francesca; Ferrarin, Maurizio (Frontiers in Human Neuroscience, 2019)
Previous evidence has shown that tool-use can reshape one’s own body schema, extending peripersonal space and modulating the representation of related body parts. Here, we investigated the role of tool action in shaping the body metric representation, by contrasting two different views. According to a first view, the shaping would rely on the mere execution of tool action, while the second view suggests that the shaping induced by tool action on body representation would primarily depend on the representation of the voluntary motor programs. To this aim, we contrasted a condition in which participants voluntarily accomplish the movement by representing the goals and programs of tool action (i.e. active tool-use training) with a condition in which the tool-use training was produced without motor intentionality (i.e. passive tool-use training by means of robotic assistance). If the body metric representation primarily depends on coexistence between intention and action, we would expect an increase of the perceived forearm length in the post- with respect to the pre-training phase after the Active training phase only. Healthy participants were asked to estimate the midpoint of their right forearm before and after 20 minutes of tool-use training. In the Active condition, subjects performed “enfold-and-push” movements using a rake to prolong their arm. In the Passive condition, subjects were asked to be completely relaxed while the movements were performed with robotic assistance. Results showed a significant increase in the perceived arm length in the post- with respect to the pre-training phase only in the Active task. Interestingly, only in the post-training phase, a significant difference was found between Active and Passive conditions, with a higher perceived arm length in the former than in the latter. From a theoretical perspective, these findings suggest that tool-use may shape body metric representation only when action programs are motorically represented and not merely produced. From a clinical perspective, these results support the use of robots for the rehabilitation of brain-damaged hemiplegic patients, provided that robot assistance during the exercises is present only "as-needed" and that patient's motor representation is actively involved.